2007
DOI: 10.1523/jneurosci.4912-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Early Cross-Modal Interactions in Auditory and Visual Cortex Underlie a Sound-Induced Visual Illusion

Abstract: When a single flash of light is presented interposed between two brief auditory stimuli separated by 60 -100 ms, subjects typically report perceiving two flashes (Shams et al., 2000, 2002). We investigated the timing and localization of the cortical processes that underlie this illusory flash effect in 34 subjects by means of 64-channel recordings of event-related potentials (ERPs). A difference ERP calculated to isolate neural activity associated with the illusory second flash revealed an early modulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
233
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(264 citation statements)
references
References 51 publications
27
233
4
Order By: Relevance
“…The auditory-induced double-flash, a phenomenon wherein a single flash of light paired with two or more brief auditory events is perceived as multiple flashes of light (Shams et al, 2000;Mishra et al, 2007), has also been reported for the somatosensory modality (Violentyev et al, 2005), which correlates with activity in visual and somatosensory areas (Lange et al, 2011). In our paradigm (Fig.…”
Section: Stimuli and Proceduressupporting
confidence: 72%
“…The auditory-induced double-flash, a phenomenon wherein a single flash of light paired with two or more brief auditory events is perceived as multiple flashes of light (Shams et al, 2000;Mishra et al, 2007), has also been reported for the somatosensory modality (Violentyev et al, 2005), which correlates with activity in visual and somatosensory areas (Lange et al, 2011). In our paradigm (Fig.…”
Section: Stimuli and Proceduressupporting
confidence: 72%
“…One relevant point here is the integrative vs. segregative nature of the task with regard to multisensory processing: experimental paradigms using multisensory integration have classically reported an increase of sensory evoked responses, for instance when using the sound-induced flash illusion (Mishra et al, 2007;Watkins et al, 2006). In a TOJ task however, the segregation of auditory and visual information is a pre-requisite for successful ordering of auditory and visual events in time.…”
Section: Evoked Activity and Attention To Timementioning
confidence: 99%
“…If that is the case, we would expect familiar and unfamiliar objects to be processed differently in the context of the sound-induced flash illusion. The sound-induced flash illusion represents a good way to test the role of visual familiarity in early audio-visual interactions because the illusion originates early in the processing stream [21,27,30,35] and because audition, not vision, dominates in this task [28][29].…”
Section: Page 5 Of 21mentioning
confidence: 99%
“…Integration of the audio-visual stimuli of the flash illusion appears to occur at early stages of stimulus processing [21,27,30,35] and it is linked to activity in the visual cortex (V1) although it is unclear whether the activity in V1 is due to direct inputs from the primary auditory cortex or to back-projections from the superior temporal polysensory area [35]. As for the time course of familiar stimuli processing, evidence from face recognition studies shows that recognising a face as familiar involves a series of processes [3], including the processing of visual features of familiar individuals, then the unique semantic information associated to the person, and then his/her name (see also [16]).…”
Section: Page 5 Of 21mentioning
confidence: 99%
See 1 more Smart Citation